1994
DOI: 10.1021/ma00082a013
|View full text |Cite
|
Sign up to set email alerts
|

Component Dynamics Miscible Polymer Blends: A Two-Dimensional Deuteron NMR Investigation

Abstract: The dynamics of individual components in 1,4-polyisoprene/poly(vinylethylene) miscible blends are studied using two-dimensional deuteron exchange NMR. The rate of the backbone reorientation process near the glass transition is quantitatively determined for each species in a miscible blend as a function of temperature. We demonstrate that the broad glass transition arises both from a wide distribution of segmental motional rates for each species and from intrinsic differences in the motional rate between the tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

14
395
2
2

Year Published

1999
1999
2011
2011

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 224 publications
(413 citation statements)
references
References 11 publications
14
395
2
2
Order By: Relevance
“…1,4 Similar bimodal mobilities of components are reported for various systems consisting of large and small molecules. 5,6,9,10 This behavior is not in harmony with a generally believed view of cooperativity [14][15][16][17][18] of local motions in supercooled liquids near the glass transition temperature T g . For instance if the PS chains and the toluene molecules in the PS/toluene system move cooperatively, the splitting into the two different relaxation processes would not occur.…”
mentioning
confidence: 58%
See 2 more Smart Citations
“…1,4 Similar bimodal mobilities of components are reported for various systems consisting of large and small molecules. 5,6,9,10 This behavior is not in harmony with a generally believed view of cooperativity [14][15][16][17][18] of local motions in supercooled liquids near the glass transition temperature T g . For instance if the PS chains and the toluene molecules in the PS/toluene system move cooperatively, the splitting into the two different relaxation processes would not occur.…”
mentioning
confidence: 58%
“…1/3 of the 5CB molecule and does not move cooperatively with PS but the 5CB molecule does. From the intensity of the α and β peaks, the fraction of the 5CB molecules moving cooperatively with PS has been estimated to be 0.25 and 0.63 for the blends containing 30 and 20 wt% of 5CB, respectively.KEY WORDS Polystyrene / 4-n-Pentyl-4 -cyanobiphenyl / Dielectric Relaxation / Dynamical Heterogeneity / Cooperativity / Diluent / Segmental Motion / Dynamics of low molecular weight molecules dissolved in polymer matrices has been studied long by means of dielectric, 1-8 mechanical, 7, 8 NMR,6,7,9,10 light scattering, 7 fluorescence depolarization, 11 ESR,12 and thermal methods. 6, 13 Adachi et al 4 and Yoshizaki et al 1 reported the dielectric behaviors of the systems consisting of polystyrene (PS) and alkylbenzene such as toluene, ethylbenzene and butylbenzene.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…While this difference is just barely significant, given the error bars, it is consistent with a trend seen in some miscible polymer blends, i.e., that each component retains its own temperature dependence in the blend. 32 …”
Section: Resultsmentioning
confidence: 99%
“…The final properties of the blend depend on the properties of the pure polymer components, miscibility and adhesion between the phases as well as the size and uniformity of the phase texture or morphology. Many techniques have been extensively used to investigate the miscibility and molecular dynamics of polymer blends, such as, differential scanning calorimetry (DSC), 1, 2 NMR, [3][4][5][6] dielectric spectroscopy, [7][8][9][10][11][12] and mechanical measurements. [13][14][15][16][17] The dielectric relaxation spectroscopy is a powerful tool cable of providing information about the molecular dynamics and the nature of the interactions in blends by monitoring the motion of dipolar groups attached to molecular chains.…”
mentioning
confidence: 99%